Competitive interactions in two different plant species: Do grassland mycorrhizal communities and nitrogen addition play the same game? - Bahadur, Ali; Jiang, Shengjing; Zhang, Wei; Sajjad, Wasim; Usman, Muhammad; Nasir, Fahad; Amir Zia, Muhammad; Zhang, Qi; Pan, Jianbin; Liu, Yongjun; Chen, Tuo; Feng, Huyuan (Frontiers in Plant Science, 2023)
In the Tibetan Plateau grassland ecosystems, nitrogen (N) availability is rising dramatically; however, the influence of higher N on the arbuscular mycorrhizal fungi (AMF) might impact competitive plant interactions. Therefore, understanding the part played by AMF in the competition between Vicia faba and Brassica napus and its dependence on the N-addition status is necessary. To address this, a glasshouse experiment was conducted to examine whether the grassland AMF community's inocula (AMF and NAMF) and N-addition levels (N-0 and N-15) alter plant competition between V. faba and B. napus. Two harvests took days 45 (1st harvest) and days 90 (2nd harvest), respectively. The findings showed that compared to B. napus, AMF inoculation significantly improved the competitive potential of the V. faba. In the occurrence of AMF, V. faba was the strongest competitor being facilitated by B. napus in both harvests. While under N-15, AMF significantly enhanced tissue N:P ratio in B. napus mixed-culture at 1st harvest, the opposite trend was observed in 2nd harvest. The mycorrhizal growth dependency slightly negatively affected mixed-culture compared to monoculture under both N-addition treatments. The aggressivity index of AMF plants was higher than NAMF plants with both N-addition and harvests. Our observation highlights that mycorrhizal associations might facilitate host plant species in mixed-culture with non-host plant species. Additionally, interacting with N-addition, AMF could impact the competitive ability of the host plant not only directly but also indirectly, thereby changing the growth and nutrient uptake of competing plant species.